Hands-on mini projects of IoT in electrical engineering - Rubita Sudirman; Nor Aini Zakaria (Penerbit UTM Press, 2021)
This book contains information about the current methods in developing electrical and electronics mini projects using IoT. Projects were chosen based on actual community problems in the area of food industries, child safety and digital agriculture, these themes were discussed in this book. It is the most practial guide for working researchers and students who need to capitalize on the latest technologies utilizing IoT.